Development of Th1 Imprints to rBCG Expressing a Foreign Protein: Implications for Vaccination against HIV-1 and Diverse Influenza Strains. (7th June 2010) - Power, Carl; Marfleet, Travis W.; Qualtiere, Louis; Xiao, Wei; Bretscher, Peter
Abstract : We demonstrate here that immunizing naïve mice with low numbers of recombinant Bacille Calmette-Guérin (rBCG) expressing β -galactosidase (β -gal) generates predominant Th1 responses to both BCG and β -gal whereas infection with high numbers generates a mixed Th1/Th2 response to both BCG and β -gal. Furthermore, the Th1 response to both BCG and β -gal is stable when mice, pre-exposed to low numbers of rBCG, are challenged four months later with high numbers of rBCG. Thus the Th1/Th2 phenotypes of the immune responses to β -gal and to BCG are "coherently" regulated. Such rBCG vectors, encoding antigens of pathogens preferentially susceptible to cell-mediated attack, may be useful in vaccinating against such pathogens. We discuss vaccination strategies employing rBCG vectors that are designed to provide protection against diverse influenza strains or numerous variants of HIV-1 and consider what further experiments are essential to explore the possibility of realizing such strategies.